2021
DOI: 10.1021/acs.iecr.0c05915
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Meerwein–Ponndorf–Verley Reaction and Relative Side Reactions over MgO in the Process of Ethanol to 1,3-Butadiene: A DFT Study

Abstract: In this work, we performed density functional theory calculations to explore reaction pathways of ethanol to 1,3butadiene on the surfaces of MgO(100) and MgO(110). The overall activation barrier and reaction energy were calculated for the Meerwein−Ponndorf−Verley (MPV) reaction and relative side reactions, cross aldol condensation, and hydrogenation reaction. It is verified that the acidity and basicity sites on MgO(110) are stronger than those on MgO(100), which is favorable for the MPV reaction and cross ald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The para-substituted derivatives 13 b-15 b (Scheme 5) are only detected in very minor amounts. This sensitivity towards the catalyst's basic sites, especially those based on alkaline earth metal oxides, is discussed in detail in references [12,14,89,92]. The recycled catalyst MgO_2-rec, shows, however, a different catalytic behavior when compared to MgO_2.…”
Section: Catalysis Meerwein-pondorf-verley Reductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The para-substituted derivatives 13 b-15 b (Scheme 5) are only detected in very minor amounts. This sensitivity towards the catalyst's basic sites, especially those based on alkaline earth metal oxides, is discussed in detail in references [12,14,89,92]. The recycled catalyst MgO_2-rec, shows, however, a different catalytic behavior when compared to MgO_2.…”
Section: Catalysis Meerwein-pondorf-verley Reductionmentioning
confidence: 99%
“…[86] The overall mechanism of the MPV reaction is discussed in references. [84,85,[88][89][90][91] Catalysts MgO_1 and MgO_2 can be recycled by centrifugation and consecutive calcination at 400 °C in air for 24 h whereby MgO_1-rec and MgO_2-rec were obtained. Characterization of the material was done by BET and PXRD confirming that the recycled oxides exhibit similar surface areas (230 m 2 g À 1 , MgO_1-rec; 240 m 2 g À 1 , MgO_2-Rec) and comparable crystallite sizes (Table 4).…”
Section: Catalysis Meerwein-pondorf-verley Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is argued that these species are formed either via direct surface reaction between AL and ethanol, 11,90 or by Meerwein-Ponndorf-Verley (MPV) reduction of CAD, which is obtained from AL by aldol addition and condensation. 13,55,91,92 Recently, Yang et al 28 successfully identified the aldol addition product 3-hydroxybutanal (i. e., acetaldol), the intermediate of CAD, but not under commonly used reaction conditions. We never detected acetaldol and never found CAD in the product mixture in concentration that could be considered as strong enough evidence for the role of CAD or CAD-like surface species as an intermediate of the ETB reaction.…”
Section: Discussionmentioning
confidence: 99%